THE USE OF TRAINING DEVICES FOR THE DEVELOPMENT OF HUMAN MOTOR ABILITIES - Kabanov, Yu.M.; Nedosekov, Yu.V.; Gulidin, P.K.; Venskovich, D.A.; Koloshkina, V.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and excel gym fitness equipment for physical progress and rehabilitation needs. Methods and structure of the study. The gym fitness equipment development process was organized to (1) design and test fundamentally new gym fitness equipment; and (2) excel the existing fitness equipment. Results and conclusion. The gym fitness/ rehabilitation equipment of our design analyzed herein was designed to build and improve strength, speed-strength and movement coordination qualities on an individualized basis, with some trainers applicable for specific rehabilitation purposes. The hand grip, for instance, may be used for the post-injury rehabilitation of the relevant hand muscles, ligaments and tendons; the gymnastic bench may be used to recover and excel the walking movement coordination; and the gymnastic ladder to correct a range of postural and spinal disorders/ dysfunctions. We have also developed an ankle joint muscle rehabilitation and training machine. Every piece of the gym equipment of our design can be easily produced using the standard industrial equipment and readily accessible materials.